The Plastic Pathfinder: A macroplastic transport and fate model for terrestrial environments - Mellink, Y.; van Emmerik, T.; Kooi, M.; Laufkötter, C.; Niemann, H. (Frontiers in Environmental Science, 2022)
Graphical Abstract